2017
DOI: 10.1002/hed.24903
|View full text |Cite
|
Sign up to set email alerts
|

Association between radioiodine treatment for thyroid cancer and risk of stroke

Abstract: The I-131 treatment for thyroid cancer did not increase the risk of stroke during 10-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The relationship between RAI, carotid intima thickness, and subsequent atherosclerosis in thyroid cancer patients is still controversial. In our study, RAI was not associated with a higher risk of cerebrovascular disease (HR = 1.04, 95% CI = 0.74-1.20, p = 0.91), which is consistent with the established literature [25].…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between RAI, carotid intima thickness, and subsequent atherosclerosis in thyroid cancer patients is still controversial. In our study, RAI was not associated with a higher risk of cerebrovascular disease (HR = 1.04, 95% CI = 0.74-1.20, p = 0.91), which is consistent with the established literature [25].…”
Section: Discussionsupporting
confidence: 92%
“…We also postulate baseline patient age, extent of residual thyroid tissue as well as differences in underlying disease contribute discrepancy between two studies. Another recent nationwide cohort study with a 10-year follow-up from Taiwan (24) reported an HR of 0.89 (95% CI, 0.60-1.33) after adjustments for age, sex, and comorbidities, suggesting that 131 I treatment for TC did not increase the risk of stroke. These discrepancies are likely due to the studies' different underlying thyroid diseases, population parameters, and design; therefore, the inconsistent findings concerning higher cerebrovascular disease risk at lower cumulative RAI dosage and no increase risk at higher cumulative RAI dosage requires standardized international studies to acquire definite conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…In multivariate analyses after adjustments, the HR for cerebrovascular events was 1.17 (95% CI, 1.07-1.28) in hyperthyroid patients and 1.21 (95% CI, 1.02-1.44) in euthyroid patients. It should be noted, however, that the actual values of thyroid stimulating hormone (TSH), which are important discriminative factors between RAItreated patients and controls for cerebrovascular events, were not included in this study, and the median total dosage of RAI therapy (approximately 11 mCi) was relatively low compared to that used in other studies of patients with TC (9,24). We also postulate baseline patient age, extent of residual thyroid tissue as well as differences in underlying disease contribute discrepancy between two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenously suppressed TSH was found to be associated with cardiovascular morbidity and mortality in the general population [8,9] . The findings of elevated atherosclerotic cardiovascular risk factors as well as cardiovascular morbidity among TC patients also highlight the importance of a balance between benefits and detriments when considering exogenous TSH suppression for TC patients [26,27,33] . The extent of TSH suppression has also been questioned by others [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Several pathological and high-risk conditions have been found among individuals with TC in comparison to the healthy controls. Park et al [33] investigated the relationship of potential risk factors and treatment effects with cardiovascular disease outcome among 3822 TC survivors, using the state-wide Utah Population Database during a mean 8.4-year follow-up. They found a significant association between the following factors and a high risk of cardiovascular conditions: age at diagnosis (40- Izkhakov et al [28] likewise reported an elevated risk for cardiovascular morbidity among DTC survivors aged 55-64 (HR = 1.29 [1.08-1.53]) and 65-74 years (HR = 1.36 [1.14-1.61]) compared to matched controls.…”
Section: Associations Between Potential Cardiovascular Risk Factors and Cardiovascular/cerebrovascular Morbidity Among Tc Survivorsmentioning
confidence: 99%